Potential Waste from Temporary Shelters in the Area of Universitas Pertamina as Raw Materials of Refuse Derived Fuel (RDF) - Ridhosari, Betanti; Suryawan, I Wayan Koko; Rahman, Ari; Ardianto, Ardhan; Zahra, Nurulbaiti Listyendah (Universitas Diponegoro, 2024)
Universitas Pertamina has a strong vision in the energy field and is developing environmentally friendly infrastructure and management, including waste management. Considering these efforts, ‘waste-to-energy’ is an interesting concept to be developed. The practical application of this concept is exemplified by refuse-derived fuel (RDF). This research aimed to analyze the potential of waste from Universitas Pertamina’s temporary shelter as raw materials for RDF and identify the potential energy that can be produced. This research began by measuring the generation and composition of waste. Each type of waste is identified for water content, ash content, and calorific value. These findings were used to identify which waste types could serve as RDF raw materials. The water content analysis showed that, except for food waste, all waste types met RDF standards. All waste types also met the RDF ash content standards. The calorific value analysis showed that plastic waste had the highest heating value at 45.6 MJ/kg, followed by rubber waste (40.1 MJ/kg) and styrofoam (35.0 MJ/kg). Calculations for waste generation potential and heating value indicated a total potential calorific value reached 9,895.1 MJ/day. With this significant potential, Universitas Pertamina has the opportunity to develop innovative waste management, especially in producing RDF.